2002
DOI: 10.1046/j.1365-2958.2002.02844.x
|View full text |Cite
|
Sign up to set email alerts
|

Spc24 interacts with Mps2 and is required for chromosome segregation, but is not implicated in spindle pole body duplication

Abstract: Mps2 (monopolar spindle protein) is a coiled-coil protein found at the spindle pole body (SPB) and at the nuclear envelope that is required for insertion of the SPB into the nuclear envelope. We identified three proteins that interact with Mps2 in a two-hybrid screen: Bbp1, Ynl107w and Spc24. All three proteins contain coiled-coil motifs that appear to be required for their interaction with Mps2. In this work, we verified the Mps2-Spc24 interaction by co-immunoprecipitation in vivo and by the in vitro interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 42 publications
2
28
0
Order By: Relevance
“…The budding yeast Ndc80 central kinetochore complex, which is composed of the four coiled-coil proteins, Ndc80, Nuf2, Spc24, and Spc25, is required for proper attachment of chromosomes to spindle MTs and activation of the spindle checkpoint in the presence of defects in attachment (Janke et al, 2001;Wigge and Kilmartin, 2001;Le Masson et al, 2002;Montpetit et al, 2005;Pinsky et al, 2006). It has recently been shown that the kinetochore has a role in maintaining a short (1.5-2 m) spindle when DNA replication is stalled by treatment of cells with HU (Bachant et al, 2005).…”
Section: Spc24 Is Required For Viability and For Preventing Spindle Ementioning
confidence: 99%
“…The budding yeast Ndc80 central kinetochore complex, which is composed of the four coiled-coil proteins, Ndc80, Nuf2, Spc24, and Spc25, is required for proper attachment of chromosomes to spindle MTs and activation of the spindle checkpoint in the presence of defects in attachment (Janke et al, 2001;Wigge and Kilmartin, 2001;Le Masson et al, 2002;Montpetit et al, 2005;Pinsky et al, 2006). It has recently been shown that the kinetochore has a role in maintaining a short (1.5-2 m) spindle when DNA replication is stalled by treatment of cells with HU (Bachant et al, 2005).…”
Section: Spc24 Is Required For Viability and For Preventing Spindle Ementioning
confidence: 99%
“…Strains were arrested in G 1 phase using the mating pheromone aF and then released to 37°and monitored over a period of 4 hr. Multiple spc24 Ts mutants have been created yet only one arrest phenotype has been published (Janke et al 2001;Wigge and Kilmartin 2001;Le Masson et al 2002). Unexpectedly, we found that all three of our spc24 alleles displayed different arrest profiles (Figure 1, A and B).…”
Section: Resultsmentioning
confidence: 70%
“…We decided to focus on one member of the Ndc80 complex, Spc24p, which has previously been shown to have a role in MT attachment and spindle checkpoint control, and one member of the outer kinetochore Dam1 complex, Spc34p, which is required for MT attachment, spindle stability, and prevention of monopolar attachment (Janke et al 2001(Janke et al , 2002Wigge and Kilmartin 2001;Le Masson et al 2002). We were concerned that genome-wide screening using only a single mutant of spc24 and spc34 might limit our results, depending on the nature of the mutation and the resulting defect in protein function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations